Variability in resistance to clubroot in European cauliflower cultivars - Pavel Kopecký; Ivana Doležalová; Martin Duchoslav; Karel Dušek (Plant Protection Science, 2012)
Fifty genotypes of cauliflovwer (Brassica oleracea var. botrytis) were evaluated for resistance to clubroot disease (Plasmodiophora brassicae Wor.) under controlled conditions in a plant growth chamber. The cultivars with the highest resistance were Brilant, Agora, and Bora, while the most susceptible were the cultivars White Top, White Fox, and Octavian. The variation in disease index is probably due to different pathogenicity rates of clubroot pathotypes and genetic heterogeneity of European cauliflower cultivars. The obtained results will be tested in an infested and non-infested field.